Conformational transitions of the catalytic domain of heme-regulated eukaryotic initiation factor 2 alpha kinase, a key translational regulatory molecule - Sreejith, R. K.; Suresh, C. G.; Bhosale, Siddharth H.; Bhavnani, Varsha; Kumar, Avinash; Gaikwad, Sushama M.; Pal, Jayanta K. (Journal of Fluorescence, 2012)
In mammalian cells, the heme-regulated inhibitor (HRI) plays a critical role in the regulation of protein synthesis at the initiation step through phosphorylation of a-subunit of the eukaryotic initiation factor 2 (eIF2). In this study we have cloned and performed biophysical characterization of the kinase catalytic domain (KD) of rabbit HRI. The KD described here comprises kinase 1, the kinase insertion domain (KI) and kinase 2. We report here the existence of an active and stable monomer of HRI (KD). The HRI (KD) containing three tryptophan residues was examined for its conformational transitions occurring under various denaturing conditions using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The parameter A and phase diagram analysis revealed multi-state unfolding and existence of three stable intermediates during guanidine hydrochloride (Gdn-HCl) induced unfolding of HRI (KD). The protein treated with 6 M Gdn-HCl showed collisional and static mechanism of acrylamide quenching and the constants (K-sv=3.08 M-1 and K-s=5.62 M-1) were resolved using time resolved fluorescence titration. Based on pH, guanidine hydrochloride and temperature mediated transitions, HRI (KD) appears to exemplify a rigid molten globule-like intermediate with compact secondary structure, altered tertiary structure and exposed hydrophobic patches at pH 3.0. The results indicate the inherent structural stability of HRI (KD), a member of the class of stress response proteins.
Keywords: Circular dichroism (CD); eIF2 alpha kinase; Heme-regulated inhibitor; Molten globule; Steady-state and time-resolved fluorescence

Cloning, expression and in silico studies of a serine protease from a marine actinomycete (Nocardiopsis sp NCIM 5124) - Rohamare, Sonali; Gaikwad, Sushama M.; Jones, Dafydd; Bhavnani, Varsha; Pal, Jayanta; Sharma, Ranu; Chatterjee, Prathit (Process Biochemistry, 2015)
A serine protease (N. protease), from Nocardiopsis sp., was cloned and expressed in Escherichia coli and investigated for its potential kinetic stability. Protein expression using two vectors, pET-22b (+) and pET-39b (+) was compared based on proper folding and soluble expression of the protein. pET-39b (+) was found to be a better vector for soluble expression of this protease containing disulfide bonds. In silico studies were also carried out for N. protease. Homology modeling suggested N. protease to be a member of PA clan of proteases. The phylogenetic analysis showed relatedness of N. protease to kinetically stable proteases. Molecular docking studies performed exhibited interaction of a peptide substrate with catalytic pocket of the enzyme. High temperature MD simulations were performed on N. protease to study its unfolding behavior and comparisons were made with alpha LP. A novel approach to study `cooperativity' of protein unfolding was undertaken, wherein `P' value analysis based on phi and psi values of the protein was performed. Data showed sharper P value transition for alpha LP when compared to N. protease thus indicating relatively less kinetic stability of N. protease. Present study holds significance as the non-streptomycete actinomycetes group is least explored and ensures industrially important enzymes with exceptional stabilities. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Actinomycetes; Cloning and expression; Kinetic stability; Protease; Thermal simulation